Bioinspired Materials for Medical Applications. (Woodhead Publishing series in biomaterials, 2016)
Bioinspired Materials for Medical Applications examines the inspiration of natural materials and their interpretation as modern biomaterials. With a strong focus on therapeutic and diagnostic applications, the book also examines the development and manipulation of bioinspired materials in regenerative medicine. The first set of chapters is heavily focused on bioinspired solutions for the delivery of drugs and therapeutics that also offer information on the fundamentals of these materials. Chapters in part two concentrate on bioinspired materials for diagnosis applications with a wide coverage of sensor and imaging systems With a broad coverage of the applications of bioinspired biomaterials, this book is a valuable resource for biomaterials researchers, clinicians, and scientists in academia and industry, and all those who wish to broaden their knowledge in the allied field. Explores how materials designed and produced with inspiration from nature can be used to enhance man-made biomaterials and medical devices Brings together the two fields of biomaterials and bioinspired materials Written by a world-class team of research scientists, engineers, and clinicians.